Adaptive immunity at patients with chronic diseases of the stomach and intestine - N. L. Denisov; V. T. Ivashkin (Российский журнал гастроэнтерологии, гепатологии, колопроктологии, 2009)
Aim of investigation. To determine the pathogenic significance of changes of general (adaptive) immunity in patients with chronic diseases of the stomach and intestine.Material and methods. Original study included 68 patients with chronic active H. pylori-positive gastritis (CG Н.р.+), 41 – chronic active H. pylori-negative gastritis (CG Н.р.–), 34 – chronic multifocal atrophic gastritis (CMfAtrG), 36 – with peptic ulcer of the stomach (PUS), 31 patient with irritable bowel syndrome (IBS), 34 - with irritable bowel syndrome with diarrhea (IBSD), 34 - with malabsorbtion syndrome (MS), 41 – with celiac disease (CD) and 39 patients with ulcerative colitis (UC). The control group consisted of 65 generally healthy patients. Total number of T lymphocytes, along with absolute and relative contents of their subpopulations was determined by flow-cytometer EPICS C Cultronics USA and Facscan Becton Dicenson by standard procedure with application of monoclonal antibodies «ORTHO» USA, Becton Dicenson or Dako. Lymphocytes with receptors to CD3+, CD4+, CD8+ and B-lymphocytes carrying immunoglobulin receptors A, M, G were detected. Quantity of T-lymphocytes, B-lymphocytes and their subpopulations, as well as Т4/Т8 ratio and quantity of active Т-cells were analyzed in each of the specified groups of patients.Results. The contents of Т3+-cells (general T-lymphocytes marker) in peripheral blood at chronic diseases of the stomach did not differ significantly from normal range except for the group of PUS, in which this parameter significantly exceeded control values, increase of Т4+-lymphocytes concentration was found in comparison to of CG Н.р.– and CMfAtrG groups. Comparative analysis of studied adaptive immunity parameters at chronic bowel diseases showed much higher diversification of immune system changes, than at stomach diseases. The most severe disorders in subpopulation content of Т- and B-lymphocytes were observed in groups of UC and CD. At IBSD and MS they became less apparent and virtually did not differ from control values at IBS.Conclusion. Obtained data are in favor of two points. First, at UC severe elevation of activity of adaptive immunity is revealed. Second, investigation of parameters of adaptive immunity has diagnostic and differential-diagnostic value for clinical enterology and coloproctology.